AVALIAÇÃO DO PROCESSO DE DEPOSIÇÃO SUPERFICIAL POR ATRITO EM LIGA DE ALUMÍNIO AA6351-T6 SOBRE SUBSTRATO DE LIGA DE ALUMÍNIO AA5052-H32 - Perez, Juan Carlos Galvis (2016)
This study aimed to develop a detailed study of an alternative technique for surface coatings of components or structures made aluminum alloys, using the friction surfacing process. Thus, the influence of deposition process parameters was evaluated as: traverse speed and rotational speed of consumable rod in mechanical properties and metallurgical deposits made. Due to the fact that the machine used is conventional, the axial force as a process parameter was not obtained directly on the machine. To this was used as a control parameter deposition rate, which is calculated from the relationship between the manual displacements in the Z-axis (Dz) of the machine table with the total time (t) of deposition. The experiments were performed using a conventional milling machine KONE KFE-3 / BR available by machining center of SENAI Ponta Grossa-Paraná capable of generating rotational speeds up to 4200 RPM and traverse speed in the table up to 800 mm/min. aluminum alloy rods were deposited AA6351-T6 on AA5052-H32 aluminum alloy substrates using simple type layer deposition (CS) and overlay (S). After execution of the friction deposition process, the deposits obtained were characterized with regard to geometry (length, width and thickness), followed by macro- and microstructure by the techniques of stereoscopic microscopy (EM), optical microscopy (OM), scanning electron microscopy (SEM) and microanalysis by energy dispersive spectroscopy (EDS).Additionally, a microtexture analysis by EBSD technique in a scanning electron microscope with field emission (FEG-SEM) was carried out. In order to evaluate the mechanical properties along the thickness of deposits and especially the adhesion strength of the interface deposit /substrate and deposit / deposit microhardness tests and bending test at three points were conducted, respectively. The experimental results showed that the best combination of friction surfacing process parameters between traverse speed and rotational speed used had better interfacial adhesion strength of the deposits were: i) In the case of single layer deposits (CS),the deposit obtained with traverse speed of 240 mm/min and 3000 RPM rotational speed presented the best results and ii) In the case of the overlay type container (S), the best results were obtained with the traverse speed of 340 mm/min and 3000 RPM rotational speed